Sustainable Banking Issues and Challenges - Carè, Rosella (Springer International Publishing, 2018)
This book aims to provide scholars, students and practitioners with a broad analysis - both theoretical and practical - of what it means to be a sustainable bank. It provides a comprehensive overview of sustainable banking literature and practices, discussing environmental and social pressures. The book is organized into seven chapters, of which two are dedicated to practical case studies and analysis. The book features up-to-date academic literature, a broad overview on new sustainable banking models and strategies, and case studies. Sustainable Banking is a useful reference for those seeking to understand a subject of fervent discussion in an era of financial turmoil.